La norma ortográfica en el contexto de la historia de la lengua española: la utopía de la ortografía fonémica - Berta, Tibor (Acta Hispanica, 2017)
The orthographic norm is one of the social conventions responsible for the homogeneity of the language that assures the mutual comprehensibility for the speakers by moderating the heterogeneity generated by the co-existence of diatopic, diastratic and diaphasic variants and overcoming the effects of the linguistic changes produced during the evolution of the language. Throughout the course of the history of the Spanish language, the claim for a phonemic orthography, based exclusively on the inventory of phonemes, arose several times but none of the proposals achieved considerable impact. In this paper, analysing the attitude of different works on grammar and orthography, we review how the set of components that determined the concept of orthography developed from the medieval period until the present day. We also examine the question why the phonemic orthography is a utopia, that is, an ideal pursued but not reached by the users of language.